Microvascular free tissue transfer for the head and neck reconstructive in a resource-limited setting - Dos Passos, Gary (Division of Plastic and Reconstructive Surgery, 2017)
Background: Free tissue transfer has become the standard of care for the reconstruction of head and neck oncological defects. The Groote Schuur Hospital provides a microsurgical reconstructive service in a resource-limited setting, without access to venous couplers, invasive monitoring devices, modern microscopes or sophisticated pre-operative imaging. The reconstructive surgeons perform all anastomoses under x4.5 loupe magnification. Methods: A retrospective chart review was undertaken of cases performed by the service over a 3-year period. Demographic factors, indications for flap cover, operative details (flap used, duration and lowest recorded temperature), intensive care and hospital length of stay, and other outcomes were recorded and evaluated (including flap and systemic complications, donor site morbidity, haematomas as well as returns to theatre). Results: Over a 36-month period, 109 flaps for head and neck reconstruction were performed. The main indication for surgery was squamous cell carcinoma of the oral cavity. The mean operating time for resection and reconstruction was 6.02 h (range of 4 to 12 h). Virtually, all reconstructions were performed using one of either radial forearm, free fibula or anterolateral thigh flaps. We report a complete flap loss rate of 6 %. All four successful salvages were undertaken in the early (less than 24 h) post-operative period. Hypothermia intra-operatively appears to correlate very closely with pejorative outcomes. Conclusions: By restricting reconstructive options to three main 'workhorse' flaps and by utilising a simultaneous two-team approach for tumour ablation and flap elevation, success rates comparable to international standards have been achieved. Limited resources should not be regarded as an impassable barrier to providing a successful microvascular head and neck reconstructive service.